LEAN PCOS AS A DISTINCT PHENOTYPE: METABOLIC DYSFUNCTION, DIAGNOSTIC IMPLICATIONS, AND THE EMERGING ROLE OF GLP-1–BASED THERAPIES - Kaja Stolarska; Antonina Gaj-Hunter; Patrycja Rędziniak; Alicja Ruzik; Monika Rajs; Patrycja Przebieradło; Sandra Żak; Monika Kowalska; Katarzyna Żurek; Sandra Terpiłowska (International Journal of Innovative Technologies in Social Science, 2026)
Background: Polycystic Ovary Syndrome (PCOS) affects 5–26% of reproductive-age women, yet current diagnostic frameworks insufficiently distinguish metabolically distinct phenotypes, particularly lean PCOS (BMI ≤25 kg/m²). Objective: This narrative review evaluates lean PCOS as a distinct pathophysiological entity and discusses its neuroendocrine and metabolic features, diagnostic challenges, and weight-stratified classification approaches. Methods: A literature search of PubMed, Google Scholar, and clinical guidelines (2015–2026) was conducted, including meta-analyses and comparative studies of lean and obese PCOS phenotypes. Results: Lean PCOS is characterized by neuroendocrine predominance (elevated LH/FSH ratio, adrenal androgen excess), intrinsic insulin resistance independent of BMI, and altered adipokine signaling reflecting adipose tissue dysfunction. Despite relatively favorable cardiometabolic profiles, patients exhibit subclinical hepatic and vascular risk. Genetic studies confirm distinct metabolic and insulin-signaling pathway involvement. Conclusions: Lean PCOS represents a biologically distinct phenotype requiring weight-stratified diagnostic strategies and phenotype-specific therapeutic approaches, including investigation of incretin-based therapies.